The Role of System Quality and Self-Efficacy in E-Learning Users: Exploring the Determinants of Academic Achievement - Widyaningrum, Tutut; Sholihah, Qomariyatus; Haryono, Bambang Santoso (Jurnal Pedagogi dan Pembelajaran, 2024)
An e-learning conceptual model is a framework for evaluating the quality of learning systems and outcomes. The results of the BAN-PT assessment show that the values for academic and non-academic achievement indicators are still low, this indicates that there are challenges that need to be overcome in implementing e-learning. This study aims to analyze the role of system quality and self-efficacy on e-learning use and user satisfaction that affect academic performance by developing the D&M IS Success Model. The study was an explanatory quantitative survey design model with 40 structured questionnaire items sent online. 66 respondents were sampled, taken using purposive sampling method with the Taro Yamane formula at a significance level of 10% of the population of undergraduate psychology students of 197 students. PLS-SEM method was used in analyzing the connection of exogenous and endogenous variables simultaneously. The research findings show that the overall q square value of the contribution of exogenous variables to academic performance through use and user satisfaction is 95.4% and exogenous variables affect academic performance by 75%. Self-efficacy has a positive and significant effect on use and user satisfaction with t-statistic values of 3.761; 2.422 and p-values of 0.000; 0.016, respectively. User satisfaction has a positive effect on academic performance with a path coefficient value of 0.588. E-learning evaluation allows measuring the success of implementing e-learning in achieving increased academic achievement.